2021
DOI: 10.1002/cncr.33536
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposures and risk of nasopharyngeal carcinoma in a high‐risk area: A population‐based case‐control study

Abstract: BACKGROUND:The potential role of occupational exposures in the development of nasopharyngeal carcinoma (NPC) remains unclear, particularly in high-incidence areas. METHODS: The authors conducted a population-based case-control study, consisting of 2514 incident NPC cases and 2586 randomly selected population controls, in southern China from 2010 to 2014. Occupational history and other covariates were self-reported using a questionnaire. Multivariate logistic regression was used to estimate odds ratios (ORs) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
(107 reference statements)
0
7
1
Order By: Relevance
“…In some previous studies, frequent exposure to cotton dust has been associated with elevated risk of NPC [12,21,30]. We did not find an elevated SIR among female textile workers, and there was a statistically significant decreased SIR for male textile workers.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…In some previous studies, frequent exposure to cotton dust has been associated with elevated risk of NPC [12,21,30]. We did not find an elevated SIR among female textile workers, and there was a statistically significant decreased SIR for male textile workers.…”
Section: Discussioncontrasting
confidence: 73%
“…Exposure to occupation-related agents such as formaldehyde and chlorophenol, wood and cotton dust, smokes, and combustion have been associated with the development of NPC [7][8][9][10][11][12]. Upper airways including the nasopharynx are directly affected by these often work-related exposures.…”
Section: Introductionmentioning
confidence: 99%
“…Consumption of alcoholic beverages has increased dramatically since the late 1970s in China, and high-risk drinking has reached epidemic proportions, with average annual percapita alcohol consumption rising from 2.5 L in 1978 to 4.9 L in 2009 [19]. Meanwhile, more people participate in industrial production due to rapid economic development, which may increase occupational risks including dust and chemical smoke exposure, and may have also contributed to the increased NPC occurrence [20]. Previous studies have indicated that the number of workers exposed to silica dust in China increased from 12 million in 2004 to 23 million in 2009 [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Our study indicated that the RRs of NPC incidence increased monotonously in males over all periods, and increased in females after 2010. Regarding males, this may be related to their above-mentioned continuing increase in NPC risk factor exposure [20]. For females, although their exposure to risk factors such as smoking and drinking is lower than for males, exposure to NPC risk factors continues to increase with constant changes in Chinese culture and large improvements in the social economy.…”
Section: Discussionmentioning
confidence: 99%
“…This leads one to ponder what factors could contribute to the discrepancy in EBV infection and nasopharyngeal carcinogenesis. Occupational exposures, exhausts, smoke, and caustic agents are also associated with increased risk of NPC, both in endemic regions and otherwise [169]. Diet and air quality have also been linked to disease incidence [144].…”
Section: Does the Microbiome Play A Role In Nasopharyngeal Carcinogen...mentioning
confidence: 99%